Modification of the existing maximum residue levels for isofetamid in tomatoes, peppers, aubergines, okra and cucurbits with edible peel - Brancato, Alba (EFSA J, 2018)
In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant ISK Biosciences Europe N.V. submitted a request to the competent national authority in Belgium, to modify the existing maximum residue levels (MRL) for the active substance isofetamid in tomatoes, sweet peppers/bell peppers, aubergines/eggplants, okra/lady's fingers and the whole subgroup of cucurbits with edible peel. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the commodities under evaluation. Adequate analytical methods for enforcement are available to control the residues of isofetamid in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of isofetamid according to the reported agricultural practices is unlikely to present a risk to consumer health. The reliable end points appropriate for use in regulatory risk assessment are presented.